Incendies [videorecording (DVD)] - Villeneuve, Denis, 1967-; Villeneuve, Denis, 1967-; Azabal, Lubna; Désormeaux-Poulin, Mélissa; Gaudette, Maxim, 1974-; Girard, Rémy; Mouawad, Wajdi (Sony Pictures Home Entertainment, 2011)
After the death of their mother, a set of twins make a life-altering discovery. The pair travels to the Middle East on a mission to uncover the truth about the father they thought was dead, and the brother they never knew existed. Along the way they will piece together the story of the woman who brought them into the world, discovering a tragic fate as well as the courage of an exceptional woman.